2022
DOI: 10.1161/jaha.121.023997
|View full text |Cite
|
Sign up to set email alerts
|

Association of HIV Serostatus and Inflammation With Ascending Aortic Size

Abstract: Background The prevalence and extent of subclinical large vessel vasculopathy is not well defined among people living with HIV. We aimed to evaluate associations between aortic root and ascending aortic sizes measured by 2‐dimensional transthoracic echocardiography and HIV serostatus, and to identify risk factors for larger aortic sizes among men with HIV, including levels of circulating inflammatory markers. Methods and Results Using clinical and echoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Moreover, patients with lower CD4 counts had significantly larger aortic dimensions; however, the prevalence of AA (> 5 cm) was relatively low at 0.15%. 7 In addition, similarly to Høgh et al 8 and Subramanian et al, 23 viral load was not associated with increased aortic diameter.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Moreover, patients with lower CD4 counts had significantly larger aortic dimensions; however, the prevalence of AA (> 5 cm) was relatively low at 0.15%. 7 In addition, similarly to Høgh et al 8 and Subramanian et al, 23 viral load was not associated with increased aortic diameter.…”
Section: Discussionmentioning
confidence: 57%
“…5,6 We recently reported larger aortic root and ascending aorta diameters among HIV seropositive men compared to HIV seronegative referents. 7 Recent analysis of a prospective cohort from Copenhagen showed a fourfold increased risk of aortic aneurysms (AA) among people living with HIV compared with HIV seronegative cohort participants (OR: 4.51; 95% CI: 2.56–8.08, p < 0.001). 8 Given the higher prevalence of AA with advancing age and the increased longevity of people living with HIV, it would be expected that the incidence of AA will subsequently increase in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Høgh et al has shown a direct association between HIV and TAA aneurysms. It was found that there was a four-fold higher odds of aortic aneurysms compared to uninfected controls likely due to the proinflammatory state associated with HIV ( 8 , 9 ). Given that Southern Africa has amongst the highest rates of people living with HIV globally, HIV is thus an important cause of aortic aneurysms in this population ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%